How do flexible working time policies, telework from home and work fatigue impact on the work-life balance? - Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier; Mota Veiga, Pedro; Sampaio Rodrigues, Felipe (Emerald, 2025)
Purpose: Human resource management (HRM) has become one of the main tools for improving organisational performance and satisfaction. Numerous research studies have shown the importance of promoting work-life balance (WLB), as it influences individual and family well-being. In this context, organizations are looking for strategies such as flexible working hours (FWH) or telecommuting from home to facilitate WLB. The aim of this study is to analyse how these practices, together with physical and mental fatigue, impact both WLB and overall performance, offering implications for HRM. Methodology: A theoretical model with 4 variables was designed. To test the hypotheses, a structural equation model with partial least squares was applied. A subsample of 13,724 responses from the 2021 special edition of the European Working Conditions Telephone Survey was analysed. Findings:Teleworking from home (TWH) is shown to negatively impact WLB, highlighting the challenges of balancing work and personal spheres simultaneously. However, the impact of TWH on work fatigue was not statistically significant. In contrast, flexible work schedule policies showed a positive impact on both improving WLB and reducing work-related fatigue (WF). Furthermore, WF emerged as a key factor in the relationship between flextime and WLB, but not in the relationship with TWH. Finally, TWH acted as a moderator in the relationship between flextime and WLB, suggesting that the combination of both practices contributes to reduced fatigue and improved WLB. Practical implications: This study offers key guidance for the design of human resource policies focused on employee well-being. Findings show that combining home-based teleworking with flexible schedules enhances WLB and reduces WF. Organisations can improve performance and job satisfaction by adopting strategies that integrate both practices. Additionally, clear boundaries for digital disconnection and workload adjustment are recommended.
Keywords: Teletrabajo; Horario flexible; Satisfacción en el trabajo; Flexible working hours; Work-life balance; EWCTS; Teleworking from home; Work-related fatigue